A Strategic Model to Strengthen the Brand of Senior Sports - Su Guiyu; Prin Laksitamas (Integrated Journal for Research in Arts and Humanities, 2022)
In recent years, with the rapid development of social economy, the country has paid more and more attention to the development of sports industry, and along with the arrival of aging society, the quality of life of the seniors has also received more and more attention from the society. With the increase of the seniors population, the seniors have become a force to be reckoned with in the sports market. Senior people have free time, pay attention to health, have a fixed income, and senior people buy sports products affordable, safe and convenient. With the development of sports industry, senior sports have gradually become a "sunrise industry" in the development of sports industry, and the development of participatory and healthy sports products and the health needs of the seniors are being paid more and more attention to, so the research on the strengthening of senior sports brands has important theoretical and practical significance.